Childcare Teachers' Attitudes toward the Integration of Care and Education in Korea. Issue 1 (March 2017) - Park, Soyeon; Yang, Sungeun; Sims, Margaret
THIS STUDY EXPLORES KOREAN childcare teachers' attitudes toward the integration of care and education and the primary issues related to such integration. Ninety-three childcare teachers (91 females and two males) residing in the Seoul metropolitan areas of South Korea participated in this study. Most teachers in this study believed that combining care and education would enhance the professionalisation of the early care and education field and enable better services for children. The teachers expected the following fundamental elements from the integration: heightened criteria for teacher certifications; better work conditions for teachers; age-specific standardised curricula; and improvements to the quality of facilities because of consolidated administration and management. However, the teachers were concerned with possible challenges in the childcare field after integration and its impact on childcare teachers' job opportunities. The teachers' perspectives voiced in this study offer timely data that may facilitate the development of specific guidelines and directives for the integration of care and education. Implications from this study may also contribute valuable information to other countries experiencing similar challenges in combining early education and care.